2007
DOI: 10.1007/s10529-007-9365-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pseudomonas mendocina, or recombinant Escherichia coli cells expressing toluene-4-monooxygenase, and a cell-free tyrosinase for the synthesis of 4-fluorocatechol from fluorobenzene

Abstract: The transformation of fluorobenzene (FB) by whole cell expressing toluene-4-monooxygenase (T4MO) resulted in the formation of various hydroxylated products. The predominant product was either 4-fluorophenol (4FP) or 4-fluorocatechol (4Fcat) depending on the ratio of biocatalyst to substrate concentration. The transformation of 1 mM FB by whole cells (1.5 mg CDW/ml) gave a 52% yield of 4Fcat as a single product. The yield of 4Fcat was improved 1.6-fold (80%) by adding 10 mM ascorbic acid to the biotransformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…lxxxii Only trace amounts of benzylic hydroxylation were observed, and even the slowest reactions proceeded at a rate within a factor of 3 of the native reaction. This activity was exploited in later syntheses of 4-fluorocatechollxxxiii and hydroxytyrosollxxxi. XMO also accepts a range of toluene derivatives, and whole-cell biocatalysts expressing this enzyme ( Pseudomonas putida mt-2 ) have been used for the benzylic oxidation of these compounds (Fig.…”
Section: Enzymatic C-h Functionalization As a Synthetic Toolmentioning
confidence: 99%
“…lxxxii Only trace amounts of benzylic hydroxylation were observed, and even the slowest reactions proceeded at a rate within a factor of 3 of the native reaction. This activity was exploited in later syntheses of 4-fluorocatechollxxxiii and hydroxytyrosollxxxi. XMO also accepts a range of toluene derivatives, and whole-cell biocatalysts expressing this enzyme ( Pseudomonas putida mt-2 ) have been used for the benzylic oxidation of these compounds (Fig.…”
Section: Enzymatic C-h Functionalization As a Synthetic Toolmentioning
confidence: 99%
“…Although the formation of 4-nitrocatechol from nitrobenzene accounts for less than 5% of the total product formed , 4-fluorocatechol is the sole product formed from fluorobenzene depending on the biotransformation conditions used (Nolan and O'Connor 2007). In an attempt to improve 4-fluorocatechol formation, the combination of T4MO and tyrosinase for the conversion of fluorobenzene to 4-fluorocatechol was demonstrated by our research group (Table 2) (Nolan and O'Connor 2007).…”
Section: 4-substituted Catecholsmentioning
confidence: 98%
“…Initial studies reported that T4MO catalysed the first hydroxylation of toluene to predominantly p-cresol and further metabolism of this intermediate was catalysed by subsequent enzymes in the pathway (sidechain) attack (Whited and Gibson 1991). However, during investigations with recombinant strains expressing T4MO, it was shown that T4MO can catalyse the sequential hydroxylation of benzene, nitrobenzene and fluorobenzene to catechol, 4-nitrocatechol and 4-fluorocatechol, respectively, via their respective phenolic derivatives Tao et al 2004b;Nolan and O'Connor 2007). These findings are significant as nitrocatechols are useful precursors for the synthesis of pharmaceutical drugs, such as Flesinoxan, while fluorinated compounds have the ability to influence biological activity (e.g.…”
Section: 4-substituted Catecholsmentioning
confidence: 99%
See 2 more Smart Citations